SINERGITAS PEMERINTAH DAERAH DENGAN MASYARAKAT TERHADAP KETERSEDIAAN PANGAN SEKTOR BERAS DAN IKAN DI KABUPATEN ROKAN HULU TAHUN 2016-2018 - Afrianti, Desra; Anwar, Khairul (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
Food availability in an area has a very important role to fulfill population demand for growth, maintenance and improvement of health status as well as increasing community intelligence. The issue of food availability in the regions is not done by local governments alone, but requires coordination with other stakeholders. This means that there needs to be a synergy between the government and the community. The low regional capacity of Rokan Hulu Regency in providing food for the population and the high dependence on food supply from outside the region, is both a challenge and an opportunity for the community.The purpose of this study was to determine how the synergy between the local government and the community towards the food availability in the rice and fish sector in Rokan Hulu Regency 2016-2018. This study uses a qualitative approach with descriptive methods. In collecting data, the writer used interview and documentation techniques.The results of this study indicate that the fulfillment of food availability in the rice and fish sector in Rokan Hulu Regency 2016-2018 is manifested by a synergy that combines two or more elements to get better output. Synergy is built through communication and coordination by the Rokan Hulu Regency Food and Fisheries Security Service with the community, with the aim of realizing food availability which is a food security sub-system. Insufficient food production to meet food needs is carried out by the market mechanism by the community. The Department of Food Security and Fisheries of Rokan Hulu Regency as a bureaucracy in the concept of bureaucratic performance has met several indicators in measuring bureaucratic performance.Keywords: Bureaucracy, Society, Communication, Coordination, Food Security